2018
DOI: 10.1038/s41598-018-24736-x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Enhanced Superconductivity in Epitaxial Thin Film WTe2

Abstract: In conventional superconductors an external magnetic field generally suppresses superconductivity. This results from a simple thermodynamic competition of the superconducting and magnetic free energies. In this study, we report the unconventional features in the superconducting epitaxial thin film tungsten telluride (WTe2). Measuring the electrical transport properties of Molecular Beam Epitaxy (MBE) grown WTe2 thin films with a high precision rotation stage, we map the upper critical field Hc2 at different te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 41 publications
2
40
0
Order By: Relevance
“…To further verify the structural phase of the obtained pure WTe 2 and Cr 0.02 -WTe 2 single crystals, room temperature Raman characterization was performed using an excitation wavelength of 532 nm, as shown in Figure 1e. Notably, the pure bulk WTe 2 exhibited five characteristic Raman peaks labeled as A 2 4 (112.3 cm -1 ), A 1 3 (117.4 cm -1 ), A 1 4 (133.6 cm -1 ), A 1 7 (164.4 cm -1 ), and A 1 9 (212.1 cm -1 ), which was in good agreement with the previous report of Td-phase WTe 2 [30] and consistent with our previous XRD spectra. We also found that the relative peak intensity of the A 1 7 (A 1 7 /A 1 9…”
Section: Preparation Of Pure and Cr-doped Wte 2 Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further verify the structural phase of the obtained pure WTe 2 and Cr 0.02 -WTe 2 single crystals, room temperature Raman characterization was performed using an excitation wavelength of 532 nm, as shown in Figure 1e. Notably, the pure bulk WTe 2 exhibited five characteristic Raman peaks labeled as A 2 4 (112.3 cm -1 ), A 1 3 (117.4 cm -1 ), A 1 4 (133.6 cm -1 ), A 1 7 (164.4 cm -1 ), and A 1 9 (212.1 cm -1 ), which was in good agreement with the previous report of Td-phase WTe 2 [30] and consistent with our previous XRD spectra. We also found that the relative peak intensity of the A 1 7 (A 1 7 /A 1 9…”
Section: Preparation Of Pure and Cr-doped Wte 2 Crystalsmentioning
confidence: 99%
“…Since the discovery of the nonsaturating magnetoresistance in van der Waals layered Td‐WTe 2 , [ 1 ] this material has increasingly attracted extensive interest in vastly different research fields. For example, both bulk Td‐WTe 2 under pressure [ 2 ] or intercalated [ 3 ] and WTe 2 thin film under a magnetic field [ 4 ] or proximity condition [ 5,6 ] show superconductivity. Additionally, bulk Td‐WTe 2 has also been verified to be a type‐II Weyl semimetal both theoretically [ 7 ] and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting thing is that the anisotropy of superconductivity becomes very weak at 98.5 kpa by changing the magnetic field angle [ 39 ]. The critical temperature of superconductivity can also be enhanced by in-plane magnetic fields, although it may suppress the superconductivity because of the competition between thermodynamic and magnetic energies [ 40 ]. Also, complicated chemical doping can be avoided by controlling the pressure.…”
Section: Structure and Characteristics Of Wtementioning
confidence: 99%
“…Superconductivity in low carrier density materials, such as WTe 2 [1][2][3], SrTiO 3 [4,5], ZrNCl [6,7], twisted bilayer [8][9][10] and trilayer graphene [11][12][13], is a subject of intense interest. In conventional electron-phonon superconductors, the vast difference between Fermi and Debye energies is responsible for the retarded nature of the phonon-mediated attraction.…”
Section: Introductionmentioning
confidence: 99%